PENGGUNAAN MEDIA VISUAL PREZI UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MEDIA PROMOSI INDOOR DI KELAS XII DKV SMK NEGERI 4 PARIAMAN - Chori Nugraha, Drs. Suib Awrus, M.Pd., Drs. Syafei, M. Ag. (Universitas Negeri Padang, 2017)
The purpose of this research is to improve student learning outcomes subjectsmedia campaign indoor through the use of visual media Prezi class XII student of SMK Negeri 4 Pariaman. This type of research is classroom action research (PTK) with the use of visual media DKV Prezi in class XII SMK Negeri 4 Pariaman. The experiment was conducted as many as two cycles, means of data collection using observation sheet teacher, student observation sheet and format of learning outcomes assessment, data is processed using a percentage formula. The results of data processing showed an increase learning outcomes. The results of the first cycle of learning 70.50 and the second cycle increased 80.33. Obtaining the results of study showed significant improvement. It was concluded that the use of visual media Prezi can improve student learning outcomes.